A novel edge center-based gradient-smoothing element method for 2D and 3D coupled thermoelasticity analyses. (15th January 2023) - Tang, Jinsong; Chen, Guangsong; Ge, Yao
Highlights: We present an edge center-based gradient-smoothing element for thermoelasticity. Gradient smoothing is based on edge center to obtain smoother gradient field. Superior performance is demonstrated in 2D and 3D analyses. Abstract: In this paper, an edge center-based gradient-smoothing element method is proposed for coupled thermoelasticity problems. The main achievement in our work is to construct the linear gradient field inside the element and ensure the consistency of gradient at the junction center of the element, including edge center of triangular element and face center of tetrahedral element. Hence, smoother stress and temperature gradient fields using low-order element are obtained in coupled thermoelasticity analysis without additional post-processing. With the proposed methods, superior accuracy and convergence characteristics are demonstrated compared with other methods through a series of 2D and 3D numerical tests.